Is it time for rate hikes? The Fed cannot engineer a soft landing but risks stagflation by trying - Yeva Nersisyan; L. Randall Wray (Levy Economics Institute of Bard College, 2022)
Roughly two years into the economic recovery from the COVID-19 crisis, the topic of elevated inflation dominates the economic policy discourse in the United States. And the aggressive use of fiscal policy to support demand and incomes has commonly been singled out as the culprit. Equally as prevalent is the clamor for the Federal Reserve to raise interest rates to relieve inflationary pressures. According to Research Scholar Yeva Nersisyan and Senior Scholar L. Randall Wray, this narrative is flawed in a number of ways. The problem with the US economy is not one of excess of demand in their view, and the Federal Reserve will not be able to engineer a "soft landing" in the way many seem to be expecting. The authors also deliver a warning: excessive tightening, combined with headwinds in 2022, could lead to stagflation. Moreover, while this recovery looks robust in comparison to the jobless recoveries and secular stagnation that have typified the last few decades, in Nersisyan and Wray's estimation there are few signs of an overheating economy to be found in the macro data. In their view, this inflation is not centrally demand driven; rather dynamics at the micro-level are playing a much more central role in driving the price increases in question, while significant supply chain problems have curtailed productive capacity by disrupting the availability of critical inputs. The authors suggest there is a better way to conduct policy-one oriented around targeted investments that would increase our real resource space. This will serve not only to address inflationary pressures, according to Nersisyan and Wray, but also the far more pressing climate emergency.
Keywords: 330; Monetary Policy; Inflation; Interest Rates; COVID-19; Federal Reserve